Avaliação histológica do reparo em enxertos de derme acelular, estimulado por laser não ablativo - Silveira, Vinicius Salim (2012)
This study aimed to evaluate the integration of an acellular dermal matrix graft (AlloDerm®; LifeCell Corp., The Woodlands, TX) at the implantation site and to compare integration rates between groups receiving and not receiving nonablative laser treatment by the quantification of fibroblasts within the graft and assessment of the healing process and inflammatory response around the graft. Standard 5-mm2 AlloDerm® sheets were implanted into the subcutaneous tissue in the calvaria of 32 Wistar rats (Rattus Norvegicus). Laser therapy was given at a dose of 4 J/cm2 per session immediately after surgical intervention, followed by 3 additional applications at 48-h intervals. The animals were killed 1, 3, 7, and 14 days after surgery. The specimens were stained with hematoxylin-eosin (HE). Analysis of the slides showed a significantly higher amount of edema in the control group at all observation time points, compared to the laser-irradiated group. Absence of neutrophilic inflammatory infiltrate was observed in the laser-irradiated group at all time points, but a significant amount of this infiltrate was found in the control group at 3 of the 4 observation time points. Lymphocytic infiltration was evident as early as the first observation time point in laser-irradiated animals, whereas in controls this type of infiltration was observed only after the second time point. In addition, the control group showed significantly greater revascularization than the laser-irradiated group. There was no significant difference between groups in the quantity of fibroblasts within the graft. These findings suggest that additional nonablative laser therapy is effective in the healing and integration of acellular dermal grafts.